Quantitative Study: Understanding Identity in Christ (Galatians 3:26–28) and Self-Confidence among Late Adolescents - Hasanuddin Manurung; Devrialdo Daniel Paat; Cornalia Chatryn Kase; Putri Hado (Sakura Digital Nusantara, 2026)
Purpose: This study aims to analyze the relationship between the understanding of identity in Christ based on Galatians 3:26–28 and self-confidence among late adolescents studying Christian Religious Education at State Christian Religious Higher Education Institutions in Indonesia. Methods: This study employed a quantitative approach using a correlational survey method. The sample consisted of 150 students aged 18–21 years, selected through stratified random sampling from five State Christian Religious Higher Education Institutions. Data were collected using Likert-scale questionnaires measuring students’ understanding of identity in Christ and self-confidence. The instruments were tested for validity and reliability before the main data collection. Data were analyzed using descriptive statistics and Pearson Product-Moment correlation with SPSS version 26. Findings: The results show that students’ understanding of identity in Christ was in the good category, with an actual score percentage of 78.28%. Their self-confidence was also in the good category, with a percentage of 79.94%. Correlation analysis revealed a strong and significant positive relationship between understanding identity in Christ and self-confidence, with r = 0.682 and p = 0.000. The coefficient of determination of 46.5% indicates that spiritual identity makes a substantial contribution to students’ self-confidence. Research Implications: The findings imply that strengthening students’ understanding of identity in Christ can support self-concept, emotional stability, and psychological resilience among late adolescents. Originality: This study contributes by integrating the theological concept of identity in Christ with the psychological construct of self-confidence in the context of Christian higher education in Indonesia.